The MIS 3/2 transition in a new loess profile at Krems-Wachtberg East – A multi-methodological approach. (15th January 2018) - Meyer-Heintze, Simon; Sprafke, Tobias; Schulte, Philipp; Terhorst, Birgit; Lomax, Johanna; Fuchs, Markus; Lehmkuhl, Frank; Neugebauer-Maresch, Christine; Einwögerer, Thomas; Händel, Marc; Simon, Ulrich; Solís Castillo, Berenice
Abstract: Local to regional paleoenvironmental reactions to past climate changes are preserved in loess-paleosol sequences (LPS). In order to extract this information we used a multi-methodological approach in the Upper Paleolithic site of Krems-Wachtberg East in Lower Austria. Detailed field studies and high-resolution geochemical, colorimetric, and granulometric analyses help to understand the interplay between soil formation, loess accumulation, and surface processes. In comparison to the main profile/excavation of Krems-Wachtberg 2005–2015 it can be stated that OSL- and 14 C-ages as well as the (archeological) stratigraphy of both profiles are comparable. However, pedogenic features are more evident at Krems-Wachtberg East. The new investigations show that well-established weathering indices do not clearly trace interstadial soil formation in the studied profile. Apart from this fact, single specific elements like Fe and Mg react more sensitive to initial pedogenic processes. Weak pedogenesis can further be evidenced by quantitative spectrophotometric results. The latter is also capable of refining and supporting the stratigraphy/pedology based on field analyses. As a general rule, next to loess also initial soil horizons of the MIS 3 are remarkably rich in primary carbonates indicating that soil formation took place in an alkaline environment. Due to the fact that hydrolysis of feldspars could not clearly be detected by the application of pedochemical indices, soil formation was probably limited to the oxidation of iron bearing minerals and weak carbonate leaching. These phases of favorable climatic conditions in terms of pedogenesis were terminated by increasing dust input towards the onset of MIS 2. The eolian deposits are overprinted during reducing conditions in soils and/or modified by colluvial processes. Altogether, weak pedogenesis can be reliably detected using a multi-methodological approach which leads to enhanced paleoenvironmental interpretations. The OSL-ages put the profile in a range of ∼41 to 30 ka. We present a tentative correlation of the studied loess profile to the record of the North Greenland Ice Core Project (NGRIP) for the part of the profile where OSL and 14 C complement each other.